New Thermal Insulation Materials Based on Mahogany Sawdust and Polyurethane Foam for Buildings - Gita Novian Hermana; M. Rizki Gorbyandi Nadi; M. Nur Hidajatullah; M. Nursyam Rizal (Universitas Negeri Semarang, 2023)
Global energy consumption has increased in the last few decades and is the third largest contributor to global energy consumption and one of the causes of increased carbon dioxide emissions. Therefore, in this study utilizing sawdust mahogany as a thermal insulation material to overcome the above problems. Sawdust material is combined with polyurethane foam to produce optimal physical, mechanical, and thermal insulation properties. From the study results it was found that the density of the thermal insulation material increased with the addition of sawdust. The value of the density is in the range of 0.041-0.052 gr/cm3. Observations using the secondary electron image (SEI) on thermal insulation materials show that the amount of sawdust added will affect the formation of an open pore cell structure which is directly proportional to the addition of sawdust. In addition, the more sawdust that is added will change the arrangement of cells and reduce the mechanical properties of the thermal insulation material. This is confirmed by the results of the hardness test which decreases with the addition of sawdust with the lowest value of 16.6 shore C for the addition of 10% sawdust. The thermal conductivity of the thermal insulation material has a value of 0.052, 0.038, 0.033, 0.032, and 0.033 W/mK for the addition of 0.2.5%, 5%, 7.5% and 10% sawdust, respectively. This shows that the thermal insulation material made in this study can be used as an alternative to thermal insulation material